PERAN PESERTA TRAINING DALAM MEMBANTU PENCAPAIAN KERJA ROOM BOY DI HOTEL THE SAHID RICH JOGJA - Emmita Devi Hari Putri; Muhammad Faried Wibawa (STIE Pariwisata API Yogyakarta, 2018)
The role of Room Boy is very important for the Tourism Industry, especially the hospitality industry. Hospitality is an industry that sells most major services, namely services of accommodation, facilities that provide room for the guests to stay. To prepare the room so it becomes worth selling, then this is done by room boy. Training activities especially Room Boy is very important for hotels to improve the quality of hotel employees, as well as create a mutually beneficial relationship between several parties, one of the advantages for the organizer of training activities is the employee's help during the production process. This study aims to determine the role of training participants, especially room boy in helping the achievement of room boy work at the hotel The Sahid Rich Jogja, using descriptive qualitative research methods, and using the technique of observation data collection, interviews, documentation conducted hotel location The Sahid Rich Jogja, library, which will be carried out later discussion so that can be drawn a conclusion. The results of the research indicate that there is a good impact in the location of research, among other increasing service capabilities performed by employees at the hotel, thus maximizing the efficiency of the use of labor or resources owned by the hotel.Keywords: Hotel, Room Boy Training, Achievement of Work